Genre conventions in K-pop: BTS's 'Dope' music video. Issue 5 (3rd September 2019) - Doré, Philippa; Pugsley, Peter C.
ABSTRACT: This article analyses the 2015 music video for the song 'Dope' by South Korean 'K-pop' boy-band BTS, which had attracted over 200 million YouTube views by mid-2017. We contend that such K-pop music videos draw on established genre conventions to facilitate the global commercialization of their artists. These videos act as a platform to promote, legitimize, authenticate, and consolidate the artists' place within the K-pop music industry, while facilitating artist-audience connections. As a relatively new cultural product, K-pop has emerged over the last 20 years as part of the global cultural phenomenon known as the Korean Wave, or Hallyu . The K-pop industry dates back much earlier, however, with today's K-pop representing a culmination of political, cultural, technological, and commercial factors aimed at making K-pop an integral part of South Korea's economy. By 2018, K-pop group BTS had achieved global success including top position on the Billboard charts and an invitation to address a General Assembly of the United Nations in New York. Careful design and marketing of music videos has made K-pop an important player in the global success of the Hallyu industry.